Measuring attachment to life in old age: the Portuguese version of the Positive Valuation of Life Scale (Positive VOL) - Araùjo, Lia; Ribeiro, Oscar de Andrade; Teixeira, Laetitia; Azevedo, Maria João; Jopp, Daniela; Rott, Christoph; Paúl, Constança (Quality of life research, 2015)
This study aims to present the psychometric properties of the Portuguese version of the Positive Valuation of Life Scale (Lawton et al. in J Aging Ment Healt 13:3-31, 2001).